Peran Guru Dalam Implementasi Tata Tertib Sekolah Untuk Penguatan Pendidikan Karakter Di Madrasah Tsanawiyah Darunnajah 2 Cipining Bogor - Helmi Mar'ie Muhammad; Abdul Saipon; M Nur Rochmat (PT. Banjarese Pacific Indonesia, 2024)
Nowadays, we are often disturbed by the behavior of children, especially middle school age teenagers. Because we find a lot of news that teenagers shouldn't do. Even though the aim of National education is to create complete humans, that is, humans who have knowledge and insight who are responsible for the continued development of this developing nation, so to achieve this goal, in order to form good quality students or students as resources In the future this needs to be paid attention to and prepared to answer these expectations. Creating adequate school conditions to fully develop students' abilities is the key. So, in order to realize the founder's ideals, it is necessary to draft regulations. The descriptive qualitative research method is the method used in this research. Data collection techniques are carried out through observation, interviews and documentation. From the research results, in this case it was found that the role of teachers in implementing school rules and regulations has a big impact in strengthening students' character, seen from how teachers act, and becomes a benchmark for students at school. Teachers need to be Ushwah or examples so that students can strengthen the character they have. As for the implementation of the rules and regulations, the disciplinary commission section carries out Socialization, Commitment and Enforcement, Imposing Sanctions, Evaluation and Improvement, and Continuity.